Cross-linguistic awareness in an English L4 education setting: Discovering language-specific phenomena in unrelated languages - Irsara, Martina (Glottodidactica, 2022)
This article shows how deixis and motion events prove to be ideal topics in the stimulation of reflection and enhancement of cross-linguistic awareness among South-Tyrolean speakers of Ladin, who learn English as a fourth language after Italian and German. The initial part of the article illustrates how a translation task that was focused on locative adverbials led students at upper-secondary school to recognise the extreme complexity of their own Ladin L1 adverbial system as compared to the more straightforward binary deictic system of English. The subsequent section shows how secondary-school and university students realised their difficulties in lexicalising motion events in English, arguably due to the different typological tendencies of other languages they learn or have learnt. The video clips that the study participants were asked to describe were subsequently integrated into multilingual and multimodal awareness-raising classes at primary school and in teacher education, where awareness-raising activities are fundamental.